Legal Analysis of Patent Transfer: Process, Challenges, and Implications for Rights Holders - Dinda Nuramalia; Sindi Lestari; Saidatul Husna Harahap; Suwanda Elfani Br Bangun; Mhd. Rasyid Al Anshari Lubis; Dafa Syah Bahri (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study aims to discuss the process of transferring patent rights. This study uses a normative method by examining the legal regulations, namely Law Number 13 of 2016 and Government Regulation Number 46 of 2020. And also through a literature approach to books and scientific journals in compiling this journal. The results of the study indicate that the transfer of patent rights can be done in six ways as stated in Article 74 Paragraph 1 of Law Number 13 of 2016. Analysis related to this transfer includes initial steps such as submitting a registration for the transfer of rights, challenges in registering the transfer of rights, and the implications for the rights holder. Patents themselves function to protect the inventor's rights to the invention they created so that the inventor's rights are not seized.